Penerapan Proses Wax Carving Dalam Perwujudan Produk Perhiasan Cincin Perak di Deni Jewelry - Made Mikki Bharadvaja Wirawan; I Nyoman Suardina; I Made Berata (Hastagina : Jurnal Kriya Seni, 2022)
An internship is a form of lecturing in the MBKM curriculum where students are given the means to carry out lecture activities that are carried out outside the institution. Through this internship program, students are directly involved in the world of work. This internship is a practical activity for students with the aim of gaining experience from these activities, which can later be used for professional development. The internship program is a learning activity as well as training for students so that they can understand theoretically and practically certain areas of expertise gained through direct work activities in the world of work as a form of work experience for students of the internship program (Raira, 2018). This work internship was carried out at the Deni Jewelry company in Denpasar, Bali. Currently, Deni Jewelry has a variety of decorations and types of products. one of the triggers is market demand that is always growing so this must always be with quality products in order to maintain consumer confidence. Wax carving/wax carving is a process that requires special skills in the manufacture of silver jewelry. this process is one of the determinants in realizing aesthetic silver jewelry at Deni Jewelry. The touch of the hands and the skill of the artist in shaping the wax can be "imprinted" on the product for decades or even hundreds of years to come. The wax carving process requires precision considering that jewelry tends to have small sizes and details. So in the implementation of this internship, I chose Deni Jewelry because the author can dig up information about the knowledge, skills, technology, and management that occur in it, especially the production process carried out by the Deni Jewelry company. By doing an internship at Deni Jewelry, it is hoped that the author will gain knowledge related to the topic, namely knowledge of various silver-making skills at Deni Jewelry.